PW 0373 Evaluation of the vision zero school safety zones program in the city of toronto- policy makers and researchers working together. (November 2018) - Rothman, Linda; Macpherson, Alison; Macarthur, Colin; Buliung, Ron; Fuselli, Pam; Evers, Kristen; Browne, Roger; Zeglen, Laura; Howard, Andrew
Abstract : The City of Toronto adopted its Vision Zero Road Safety Plan in July 2016, with its focus on eliminating motor vehicle collisions that result in death and serious injuries. The safety plan emphasizes a collaborative and integrative approach, involving multiple stakeholders. One of the Plan's six areas of emphasis is on school children. Stakeholders from public health, the public school board, the police, a not-for- profit organization and academic researchers have worked with the City of Toronto's Transportation Services Division to identify a package of interventions to create School Safety Zones. New interventions include physical environment changes, enforcement activities, education and support from a school traffic management facilitator. The Plan is intended to be evidence-based and data-driven. Therefore, it is essential that policy makers and researchers work together to develop appropriate evaluation strategies. Several challenges to policy makers and researchers working together exist; most of which can be overcome using a collaborative process. For example, funding cycles and priorities of granting agencies to fund academic research may not match the timelines and priorities of policy makers. Researchers prefer evidence-based priority setting and random selection to enhance scientific validity, whereas policy makers also consider political priorities and community interests. Although researchers would ideally like to maximize sample size, policy makers often have fiscal restraints. The definition of meaningful and valid outcome measurements is a challenge. Fatal and severe collisions are relatively rare, so proxy measures must be agreed upon prior to the evaluation. Regular meetings of stakeholders will help ensure evaluation that is meaningful to policy makers and scientifically sound. This process will lead to a strategy to be used by City of Toronto, Transportation Services to evaluate the effectiveness of their school zone safety interventions and can provide a model for future evaluations of Vision Zero Road Safety Plan interventions.